2016
DOI: 10.1007/s00299-015-1901-y
|View full text |Cite|
|
Sign up to set email alerts
|

PAD4, LSD1 and EDS1 regulate drought tolerance, plant biomass production, and cell wall properties

Abstract: Arabidopsis and poplar with modified PAD4, LSD1 and EDS1 genes exhibit successful growth under drought stress. The acclimatory strategies depend on cell division/cell death control and altered cell wall composition. The increase of plant tolerance towards environmental stresses would open much opportunity for successful plant cultivation in these areas that were previously considered as ineligible, e.g. in areas with poor irrigation. In this study, we performed functional analysis of proteins encoded by PHYTOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…An exactly opposite pattern was demonstrated in LSD1-OE plants. These results are consistent with our recent study which was performed on two species, Arabidopsis and Populus tremula x tremuloides, demonstrating LSD1-dependent changes in cell wall composition and cell division/cell differentiation processes (Szechyńska-Hebda et al 2016).…”
Section: Discussionsupporting
confidence: 94%
“…An exactly opposite pattern was demonstrated in LSD1-OE plants. These results are consistent with our recent study which was performed on two species, Arabidopsis and Populus tremula x tremuloides, demonstrating LSD1-dependent changes in cell wall composition and cell division/cell differentiation processes (Szechyńska-Hebda et al 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, LSD1 is a condition‐dependent scaffold protein and transcription regulator, and forms dimers with EDS1 (Czarnocka et al ). Recently, we reported that PAD4 and EDS1 can function in woody plants in a similar manner as in Arabidopsis (Ślesak et al , Szechyńska‐Hebda et al , Bernacki et al ).…”
Section: Introductionmentioning
confidence: 77%
“…Salicylic acid (SA) and reactive oxygen species (ROS), such as H 2 O 2 , are important signaling molecules that regulate CD, photosynthesis, WUE, stomatal conductance and cross‐tolerance processes (Desikan et al , Gechev and Hille , Ślesak et al , Wituszyńska et al , Wituszyńska et al , Szechyńska‐Hebda et al , Bernacki et al , Czarnocka and Karpiński ). They also play a vital role in plant development (Mittler et al , Gawroński et al ) and seed yield control (Abreu and Munné‐Bosch ).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the general agreement that the cell wall is formed via the successive deposition of cellulose, followed by lignification process, in this way, cellulose provides a key structural pattern for assembly of lignin. Lignification is a tightly regulated and dynamic process subject to post-modulation in response to abiotic and biotic stresses [30,37]. Therefore, the decrease in the porosity of the cellulose network together with the greater stability of lignin formed in cold conditions can reduce the cell wall permeability for fungus-originated enzymes and increase its mechanical strength that prevents hyphae invasion.…”
Section: Discussionmentioning
confidence: 99%